The configuration of the urban landscape in Assassin’s Creed (Ubisoft Montreal, 2007): Sources, models and referents for the recreation of its cities and monuments - Aliaga Cárceles, José Javier; Martínez Fernández, José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The Assassin's Creed videogame saga is a paradigmatic example of how to deal with the treatment of different historical periods and emblematic places. This article analyses the sources, models and references that helped to shape the urban landscapes of the Holy Land during the Third Crusade, based on the methodology of visual studies. The conclusions demonstrate that the verisimilitude achieved in the designed gamespaces transits between historical fidelity and creative freedom, which opens the door to the confluence of different art-historical styles and architectural models in Jerusalem, Masyaf, Damascus and Acre.